Factores estresantes y satisfacción laboral de la enfermera del Hospital Víctor Lazarte Echegaray Essalud - León Rojas, Yassna Carolina (2019)
This work of investigation of correlational descriptive type of cross-section, was carried out with the objective of determining the stressors and job satisfaction of the nurse in the service of emergency's Hospital Victor lazarte Echegaray, It is health Trujillo, La Libertad. The population was formed by the total of 42 nurses (you) who work in the emergency service. To collect information was applied an instrument of two parts, the first a test to determine the stress factors and the second a scale to determine the degree of job satisfaction of health personnel, to measure the statistical significance is It used the criteria "Chi - square", reaching the following conclusion: 66.7% have medium exposure to the risk of involvement, depending on the type of the personal stress factors and labor have greater predominance with a 59.5 each, depending on the degree of satisfaction a 64.3% fairly satisfied with your work. There is no relationship between the variables in study, x 2 = 4,875 with p = 0.087, being not significant